Measuring Techniques in Gas-Liquid Two-Phase Flows 1984
DOI: 10.1007/978-3-642-82112-7_17
|View full text |Cite
|
Sign up to set email alerts
|

Void Fraction Measurement by an Ultrasonic Transmission Technique in Bubbly Gas-Liquid Two-Phase Flow

Abstract: Void fraction measurement by an ultrasonic transmission technique in bubbly gas-liquid two-phase flow is developed. Numerical modelling of the experiment is conducted by using an equivalent bubble method and also by Monte Carlo simulations. Comparison of experimental and numerical results shows agreement for small void fraction conditions (e g < 0.20).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
1

Year Published

1985
1985
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 11 publications
2
22
0
1
Order By: Relevance
“…The mathematical equivalent is the convolution of the spectra given by Eqs. (7) and (8). The result, called the demodulated signal, is…”
Section: Introductionmentioning
confidence: 99%
“…The mathematical equivalent is the convolution of the spectra given by Eqs. (7) and (8). The result, called the demodulated signal, is…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al (1984) have reported a good relationship between phase holdup and attenuation. The change in acoustic velocity due to gas phase has been investigated by various researchers (Warsito et al, 1995;Soong et al, 1995;Macchi et al, 2001;Vatanakul et al, 2003;and Zheng and Zhang, 2004).…”
Section: Introductionmentioning
confidence: 89%
“…Under sterile fermentation conditions special sensors such as pressure transducers (Luo et al, 1997) may be used. It is therefore, suitable for opaque systems and has a faster response (Chang et al, 1984;Stolojanu and Prakash, 1997). Hot film anemometer probe (Karamanev et al, 1996) was also used to measure the difference of heat conductivity between liquid and gas phase.…”
Section: Gas Holdup and Mass Transfer Ratesmentioning
confidence: 99%